2017
DOI: 10.1111/crj.12698
|View full text |Cite
|
Sign up to set email alerts
|

Association between lung function, physical activity level and postural evaluation variables in adult patients with cystic fibrosis

Abstract: Lung function in patients with CF disease is associated with higher thoracic kyphosis, shorter time in moderate and vigorous PA, and shorter distance covered in 6MWT. The accelerometer has been shown to be the best instrument for assessing PA in this public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…As in other studies, we found a significant correlation between age, FEV1, and sleep quality [ 19 , 32 , 33 ]. Young patients on average have a better lung function and less comorbidities that associate with sleep disturbances.…”
Section: Discussionsupporting
confidence: 90%
“…As in other studies, we found a significant correlation between age, FEV1, and sleep quality [ 19 , 32 , 33 ]. Young patients on average have a better lung function and less comorbidities that associate with sleep disturbances.…”
Section: Discussionsupporting
confidence: 90%
“…In adults with CF, deterioration in lung function has been associated with increased dorsal kyphosis [11,36], with changes in vertical alignment of the chest [37] and also with increased prevalence of vertebral fractures [36]. These postural deviations alter the conformation of the rib cage structures, placing the respiratory muscles at a mechanical disadvantage and, therefore, may also contribute for the reduction of thorax mobility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to impaired pulmonary function, children with CF have been shown to have reduced peak cough flow (PCF) values [9], high prevalence of musculoskeletal diseases [10] and postural changes [10][11], which have been related to the severity of pulmonary involvement [11], but there are still controversies on the subject [12], which deserves to be better studied.…”
Section: Introductionmentioning
confidence: 99%
“…A consistent positive association was found between lung function ( i.e. forced expiratory volume in 1 s, FEV 1 ) and PA in all age groups, regardless of the PA measuring method (strength of conclusion: bias assessment level 2) [ 30 , 32 , 36 , 38 , 43 , 44 , 46 , 47 , 51 53 , 56 , 57 , 61 , 62 ]. A consistent positive association was found between (maximal) exercise capacity and PA in adult and mixed populations (strength of conclusion: bias assessment level 2) [ 31 34 , 36 , 53 , 54 , 63 – 66 ].…”
Section: Resultsmentioning
confidence: 70%
“…Therefore, results from this systematic review should be interpreted with caution. Subjective methods such as questionnaires are quick, easy to use and have a low cost, but are associated with difficulties including errors in subject recall (especially for children), information provided by proxies and overestimation of PA to achieve social desirability [ 54 , 61 , 89 , 90 ]. For this purpose, incorporating objective measures of PA should continue to be a priority in PA research.…”
Section: Discussionmentioning
confidence: 99%